Peach - Glass, Emma (Bloomsbury USA, 2017)
Something has happened to Peach. Staggering around the town streets in the aftermath of an assault, Peach feels a trickle of blood down her legs, a lingering smell of her anonymous attacker on her skin. It hurts to walk, but she manages to make her way to her home, where she stumbles into another oddly nightmarish reality: Her parents can't seem to comprehend that anything has happened to their daughter.